Modeling of Island Fire Station Siting Under Ship–Shore Synergy Conditions - Shengnan Li; Jingjing Guo; Boyun Liu; Xiaohan Lu; Bo Zhao (Fire)
As strategies to build a strong maritime nation are widely implemented, the importance of island ports has been increasingly highlighted, and their fire safety issues are also receiving more attention. However, at present, research on the construction of fire protection systems has mostly been focused on the interior of cities, and less research has been carried out on the linear firefighting needs of island ports. In particular, island ports are characterized by firefighting characteristics such as inconsistent mission objectives and coordinated ship-to-shore rescues, when compared to cities. In this study, a model for the siting of harbor fire stations on a cluster of distant, isolated islands is proposed, considering the costs associated with building, maintaining, and rescuing fire stations on the basis of coverage. At the same time, the loss costs associated with the response time are considered to construct an arc segment demand siting model under ship–shore synergy conditions with the objective of minimizing the total cost. The Sea Island Group is taken as an example for the analysis of the constructed site selection model. The firefighting needs and ship–shore cooperative firefighting and rescue scenarios for eight islands in the island group are the main considerations, and the model is solved using a genetic algorithm. It is concluded that the establishment of five island harbor fire stations in the Sea Island Group can balance the cost of rescue with the cost of construction. Thus, the benefits of island fire stations can be improved, satisfying coverage rates while minimizing the associated costs.